Governance of woodfuel value chains in Kenya: An analysis of policies, legislative frameworks and institutional mechanism - Sola, P.; Bourne, M.; Okeyo, I.; Njenga, M. (Center for International Forestry Research, 2020)
Successful woodfuel value chain governance is dependent on the existence of known policies that are implemented, rules and regulations that are enforced and complied with by value chain actors and institutions with capacity to regulate and render support. Kenya has formulated policies nd enacted legislation for guiding, managing and supporting woodfuel value chains. These policies and legal frameworks have evolved over the years, integrating provisions for sustainable production, distribution and use of woodfuel. However, even with well-developed policies and legislative frameworks, charcoal value chains are inadequately governed, beset by illegality, weak institutional arrangements, overlapping mandates and limited coordination and cooperation. Nonetheless, charcoal value chains have remained resilient despite the bans and moratoria throughout the decades and likely to continue in the foreseeable future. Limited knowledge, lack of incentives for sustainable production and limited support for organized efforts to manage woodfuel resources are contributing to low compliance with rules and regulations. Therefore, the development and implementation of interventions coupled with appropriate investments to incentivize and catalyze sustainable woodfuel production and trade cannot be over emphasized.